Diferentes manejos da palha de aveia preta na produtividade de milho em plantio direto - Riquetti, Neilor Bugoni [UNESP]; Sousa, Saulo Fernando Gomes de [UNESP]; Tavares, Leandro Augusto Felix [UNESP]; Correia, Tiago Pereira da Silva [UNESP]; Silva, Paulo Roberto Arbex [UNESP]; Benez, Sérgio Hugo [UNESP] (My University, 2012)
The use of oats in areas such as tillage is widely used to cover the soil and provide improved maintenance of the temperature and moisture of the soil, also to make the environment friendly to the development of micro and mesofauna, important in the process of decomposition of plant residues. A higer rate of decomposition depends directly on the size of the waste to be decomposed, because more fragmented is the residue, will decompose faster. This study aimed to evaluate the yield and some plant and ear characteristics of the corn in tillage for different straw management of black oat. The experiment was conducted at the College of Agricultural Sciences - UNESP Botucatu. Managements were performed with a roller knife, straw chopper and lack of management in two areas, one which was performed prior control to a dicots plants with 2,4-D in winter and other one without control, with a total of six treatments with four replicates. The results show no significant difference in grain yield and not for other traits studied independently of the previous control of weeds.

O uso de aveia preta é largamente utilizado em áreas de plantio direto como cobertura de solo propiciando melhoria na manutenção da temperatura e umidade do solo, além de tornar o meio favorável ao desenvolvimento da micro e mesofauna, importantes no processo de decomposição dos resíduos vegetais. Uma maior velocidade de decomposição depende diretamente do tamanho dos resíduos a serem decompostos, pois quanto mais fragmentado estiver o resíduo, mais rapidamente será decomposto. Este trabalho teve por objetivo avaliar a produtividade e algumas características da planta e da espiga da cultura do milho em sistema de semeadura direta em função de diferentes manejos da palha de aveia preta. O experimento foi instalado na Faculdade de Ciências Agronômicas – UNESP - Botucatu. Foram realizados manejos com rolo faca, triturador de palha e ausência de manejo em duas áreas, uma onde foi realizado um controle prévio de invasoras de folha larga com 2,4-D no inverno e outra sem controle, totalizando seis tratamentos com quatro repetições cada. Os resultados mostraram que não houve diferença significativa na produtividade de grãos e nem para as demais características estudadas independentemente do controle prévio de invasoras e manejo de palhada.
Keywords: Roller knife; Straw chopper; 2,4-D; Biomass; Conservation management; Rolo faca; Triturador de palha; 2,4-D; Biomassa; Manejo conservacionista